Indeterminacy of translation and impaired intersubjectivity in schizophrenia - Schönknecht, Peter; Mundt, Christoph (Psychopathology, 2013)
Impaired intersubjectivity in schizophrenia has been subject to debate in clinical psychiatry and psychotherapy. In this paper, we will discuss recent perspectives on disordered intersubjectivity among the core symptoms of schizophrenic psychoses. Based on symptoms crucial for communication deficits in schizophrenia, we address indeterminacy of translation as a potential default in the therapeutic setting. The concept of indeterminacy of translation reviewed here assumes that no reference for translation of languages is given, but principles to substitute this non-referring space of unknown terms are to be demonstrated: firstly, a maxim of indulgence which requires that as many true considerations as possible have to be achieved by the final interpretation of a proposition, and secondly, a coherence which is given when the considerations are deductable and not contradictory. Indulgence and coherence are hypothesized as reflecting an approximation process of reconstructing intersubjectivity in conditions where it is severely disturbed such as schizophrenia.
Published online: August 7, 2012
Gesehen am 15.07.2021